Mapping of ecological conditions of atmospheric air, surface and ground waters in Kharkiv region - Пересадько, В. А. (Man and Environment. Issues of Neoecology, 2014)
Key factors of atmospheric air, surface and ground waters’pollution have been determined.main directions in mapping of ecological conditions and environmental protection have been presented in the paper. Examples and contents of series of ecological maps of environment’s dynamic components of Kharkiv region have been given.